Evaluation on Flushing Operation Frequency of Sand Trap of Pendowo and Pijenan Weirs - Lilik Hendro Widaryanto (Journal of the Civil Engineering Forum, 2018)
Sediment deposited in the sand trap of Pendowo and Pijenan Weirs are influenced by the water discharge that enters the sand trap, the soil conditions next to the sand trap, and flushing time. The off schedule of the flushing time is because of the farmers’ water demand for their farming fields and fish ponds. These conditions would affect the sand trap performance. Thus, an evaluation is required. The objective of this study was to identify the performance of sand trap in Pendowo Weir and Pijenan Weir. Calculation of the irrigation water demand was aimed to identify the irrigation water discharge. Sediment that was taken from the sand trap was used to identify its index properties followed by the sediment transport calculation applying the Meyer-Peter and Muller formula. The results showed that the sand trap in Pendowo and Pijenan Weirs was still in a good performance, as indicated by their ability to hydraulically deposit and flush the sediment under frequent flushing operation in once every 6 months and 3 months during the rainy season at Pendowo and Pijenan Weir respectively. Further operation of the sand trap at both weirs with the same frequency will sustain the sand trap to function properly.